An interesting case of mycoplasma pneumonia associated multisystem involvement and diffuse alveolar hemorrhage. (2017) - Mishra, Rashmi; Cano, Edison; Venkatram, Sindhaghatta; Diaz-Fuentes, Gilda
Abstract: Severe mycoplasma pneumonia is a rare entity with only 0.5–2% of cases having a fulminant course. We present a 74-year-old woman with hypertension, diabetes mellitus and remote history of marginal zone B-cell lymphoma admitted with abdominal pain and diarrhea of 1–2 days associated with body-aches, dyspnea, dry cough and weight loss for 2–3 weeks. On physical exam, she was febrile, tachypneic, tachycardic and hypoxic on room air. Chest examination revealed diffuse crackles and end-expiratory wheezes. Laboratory tests showed anemia, acute-on-chronic kidney injury and hyaline casts and epithelial cells in the urine analysis. Chest roentgenogram and computed tomograhphy scan showed pulmonary infiltrates. Intravenous ceftriaxone and azithromycin with bronchodilators were initiated. Her clinical course was complicated by hypoxic respiratory failure, hemoptysis, and worsening of infiltrates, requiring intubation and mechanical ventilation. Bronchoscopic bronchoalveolar lavage was consistent with diffuse alveolar hemorrhage (DAH). The patient's serum was positive for IgM antibody to Mycoplasma pneumoniae [1134 U/mL] and Anti-I-specific IgM-cold-agglutining [1:40]. A diagnosis of severe mycoplasma infection with DAH was made. The patient was treated with an additional course of doxycycline, pulse dose steroids and plasmapharesis with good clinical response. Surgical lung biopsy showed focal acute lung injury. Bone marrow biopsy and fat pad biopsy were normal. She was liberated from mechanical ventilation and discharged. She returned within 24 hours of discharge with cardiac arrest and new onset right-bundle-branch-block. We hypothesize our patient had severe mycoplasma pneumonia with DAH and multisystem complications of the same including a possible venous thrombo-embolic episode leading to her demise.